Life Long Learning and Collective Experience - Henning Salling Olesen (Adult Education Research Conference, 2000)
The paper examines two aspects of collective experience and lifelong learning and invites a cross cultural discussion. The first theme concerns the historical conditions for Life Long Learning, especially in work. The second deals with the conceptual differences between German critical theory and post-modern discourses of lifelong learning.